Parental Perspectives on Respiratory Illness, Healthcare Access, and Environmental Concerns Among Children with Down Syndrome: A Qualitative Study in South Carolina - Vinita Oberoi Leedom; Daniela B. Friedman; Geoffrey I. Scott; Dwayne E. Porter; Russell S. Kirby (International Journal of Environmental Research and Public Health, 2026)
Background: Children with Down syndrome often have co-occurring physical conditions affecting well-being, and respiratory issues remain a leading cause of hospitalization and death among people with Down syndrome. Parents of children with Down syndrome experience stressors associated with respiratory illness and challenges navigating healthcare access. No prior qualitative study has examined parental perspectives on respiratory health specifically among children with Down syndrome. Identifying parental concerns can help in the development of strategies to mitigate respiratory ailments in children with Down syndrome. Methods: One-hour, semi-structured interviews were conducted among 24 families of children with Down syndrome to understand respiratory concerns. Findings were identified through codebook thematic analysis. Results: The themes identified included persistent concerns about respiratory health, repeated impact from acute and chronic respiratory issues, a rapid and unexpected decline in health during respiratory illness, insurance coverage concerns, and a lack of confidence in assessing air quality which could impact respiratory health. Conclusions: Insights gained from interviews of parents of children with Down syndrome can help policy makers identify opportunities to prevent and mitigate respiratory health problems. Findings underscore the importance of clinician responsiveness to parental concern about rapid deterioration and suggest that insurance coverage policies for this high-risk population warrant further research and policy consideration.